Lipids and spermatogenesis : very long story - Aveldaño , Marta (2019)
Our story of lipids containing PUFA with very long chains (VLCPUFA) started three decades ago with the finding, in the membranes of retinal rod outer segments, of phosphatidylcholine species that contained 22:6n-3 at sn-2 and a series of fatty acids that were elongated versions (up to C36) of common C20 and C22 PUFA (20:4n-6, 20:5n-3, 22:5n-6, and 22:6n-3) at sn-1 . Other authors found similar VLCPUFA, amide-bound to sphingosne in sphingomyelin (SM), in mammalian testis and spermatozoa.